Monster, P.I.: Validation Evidence for an Assessment of Adolescent Language That Assesses Vocabulary Knowledge, Morphological Knowledge, and Syntactical Awareness. (March 2022) - Goodwin, Amanda P.; Petscher, Yaacov; Tock, Jamie; McFadden, Sara; Reynolds, Dan; Lantos, Tess; Jones, Sara
Assessment of language skills for upper elementary and middle schoolers is important due to the strong link between language and reading comprehension. Yet, currently few practical, reliable, valid, and instructionally informative assessments of language exist. This study provides validation evidence for Monster, P.I., which is a gamified, standardized, computer-adaptive assessment (CAT) of language for fifth to eighth grade students. Creating Monster, P.I. involved an assessment of the dimensionality of morphology and vocabulary and an assessment of syntax. Results using multiple-group item response theory (IRT) with 3, 214 fifth through eighth graders indicated morphology and vocabulary were best assessed via bifactor models and syntax unidimensionally. Therefore, Monster, P.I. provides scores on three component areas of language (multidimensional morphology and vocabulary and unidimensional syntax) with the goal of informing instruction. Validity results also suggest that Monster, P.I. scores show moderate correlations with each other and with standardized reading vocabulary and reading comprehension assessments. Furthermore, hierarchical regression results suggest an important link between Monster, P.I. and standardized reading comprehension, explaining between 56% and 75% of the variance. Such results indicate that Monster, P.I. can provide meaningful understandings of language performance which can guide instruction that can impact reading comprehension performance.